Progress in the study of bioactivity, chemical composition and pharmacological mechanism of action in Wolfiporia cocos (F.A. Wolf) Ryvarden & Gilb - Xiong, Qi; Li, Zhuoran; Yang, Defeng; Liu, Xinze; Pu, Wanxu; Yue, Xitao; Jia, Kaikai; Wan, Xilin; Zou, Yuanjun (Frontiers in Pharmacology, 2025)
The Latin name of Wolfiporia cocos is Wolfiporia cocos (F.A. Wolf) Ryvarden & Gilb, it a medicinal and edible mushroom belonging to the family Polyporaceae. Traditional Chinese medicine believes that it can strengthen the spleen, diuretic, tranquillise the mind and dispel dampness. So far, the chemical and active metabolites isolated and extracted from Wolfiporia cocos are mainly polysaccharides, triterpenoids, and sterols. Modern pharmacology has found that these chemical and active metabolites have a wide range of pharmacological effects, including antitumour, antioxidation, anti-inflammatory, immunomodulation, regulation of intestinal flora, regulation of glycolipid metabolism, and improvement of organ function. By applying Poria cocos, Poria, Wolfiporia cocos, Wolfiporia cocos (F.A. Wolf) Ryvarden & Gilb as search terms, we searched all the relevant studies on Poria cocos from Web of Science and PubMed databases and classified these categories of chemical and active metabolites according to the main research content of each literature and summarized its mechanism of action, updated its latest research results, and discussed the direction of further research in the future to provide a better reference for future clinical applications with better therapeutic effects and potential medicinal value.